Effect of the heating time on the preferred growth of hydroxyapatite crystal prepared by microwave-hydrothermal technique on the defective surface of sprayed coating. (1st November 2019) - Su, Yangyang; Li, Kezhi; Wang, Jing; Xie, Wei; Zhu, Xiaofei; Wang, Changcong
Abstract: A calcium phosphate (Ca–P) coating is prepared on carbon/carbon (C/C) substrate by supersonic atmospheric plasma sprayed (SAPS) method. After that, microwave-hydrothermal (MH) method is used as the postprocessing method to lower surface defects for sprayed coating as well as obtaining uniform decomposition phase. The aim of this work is an extensive study on the preferred growth of hydroxyapatite (HA) crystals existing in the coating after MH treatment which can rapidly form in-situ growth structures to repair surface defects. The preferred orientation of these generated HA crystals is discussed. Chemical components, length-diameter ratio, particle diameter distribution, microstructure, formula derivation, thermal properties and protein adsorption of the HA crystals prepared by the MH method on sprayed coating are also studied. As a result, it is found that the MH heating time on the preferred orientation of the HA crystal appeared on sprayed coating plays an important role and the optimal crystal growth time during the MH process is 35 min. The coating after MH treatment for 250 min has the most excellent protein adsorption ability of 553 μg/disc.